Genetic Variants Associated with Vincristine-Induced Peripheral Neuropathy in Two Populations of Children with Acute Lymphoblastic Leukemia - Li, Lang (Clin Pharmacol Ther, 2019)
Vincristine is one of the core chemotherapy agents used in the treatment of pediatric acute lymphoblastic leukemia (ALL). However, one of the major toxicities resulting from vincristine exposure is vincristine-induced peripheral neuropathy (VIPN). When VIPN results in significant morbidity, the vincristine dose may need to be reduced, thus potentially decreasing the effectiveness of treatment. To date there are no robust biomarkers used clinically to determine which patients will be at risk for worse neuropathy. The current study included genome wide association analyses in two independent cohorts: Pediatric Oncology Group (POG) ALL trials and a multicenter study based at Indiana University in children with ALL. A meta-analysis of the cohorts identified two SNPS, rs1045644 and rs7963521, as being significantly (p-value threshold 0.05/4749 =1.05E-05) associated with neuropathy. Subsequently these SNPS may be effective biomarkers of VIPN in children with ALL.